Hip joint arthroplasty in complications of metal osteosynthesis of the femoral head fractures - Loskutov, Oleksandr; Oleynik, Oleksandr; Degtiar, Andrey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article contains results of the comparison of primary total hip joint arthroplasty in patients with medial fractures of the femoral neck with results of the total endoprosthesis of patients after complications of metal osteosynthesis of medial fractures of the femoral neck. The results were studied by the data of the clinical observation of 373 patients, who underwent total cementless hip joint arthroplasty for a medial fracture of the femoral neck and its sequelae, as well as by the data of statometry and with help of Harris hip score.